- Quality of Financial Report Presentation: Empirical Study from Organizational Culture - Johannes Buntoro Darmasetiawan; Rapina Rapina; Santy Setiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Organizational culture has the potential to improve the quality of financial statement presentation. Conditions that exist in several organizations in Indonesia indicate that the quality of financial statement presentation is still problematic, resulting in accounting information that is of poor quality. The purpose of this research is to look into the impact of organizational culture on the quality of financial statement presentation. The findings of this study are expected to provide a solution to problems with financial statement presentation quality. The information used in this study was gathered through a survey of 59 accounting and finance professionals in Indonesia. The data used is primary data collected through research instruments such as questionnaires and statistically processed using SPSS version 25 for Windows. The study's findings indicate that if there are issues with poor quality in financial report presentation, it is due to organizational culture that has not been optimally accommodated in information system applications for financial report presentation. Hypothesis testing in this study reveals that organizational culture has a significant influence on the quality of financial statement presentation.